Effectiveness of environmental science projects on middle school students’ environmental knowledge and attitudes - Keskin, Cansu (My University, 2019)
The aim of the study was to investigate the effects of Water Explorer Program on students' attitudes and behaviours of water usage behaviour, attitudes and environmental awareness. The study designed as a quasi experimental research. It is conducted at a state school in İstanbul 2018-2019 semesters. Four classes of 8th graders which consisted of 36 girls and 51 boys totally 87 students were the participants. . Each of the participants were randomly selected. Traditional lectures were processed in the groups which did not attend Water Explorer Program. Science projects from Water Explorer Program were processed at the groups which attended Water Explorer Program. Water usage attitudes, water usage behaviour and environmental awareness tests were applied to all groups before and after the study. In addition to pre-post tests reflection papers and worksheets were applied to Water Explorer Groups. Results of the study are that groups which attended Water Explorer Program were significantly better than other groups which did not attend the program at all tests. Therefore such projects should be increased in the science curriculum.

Bu çalışmanın amacı Su Kaşifi programının öğrencilerin su kullanımı tutum davranış ve çevre bilinçlerine etkisini araştırmaktır. Deneysel olarak tasarlanmıştır..2018-2019 yılında İstanbul'da bir devlet okulunda uygulanmıştır. Katılımcılar 36'sı kız 51'i erkek olmak üzere 87 kişiden oluşmaktadır ve rastgele seçilim yöntemi ile belirlenmişlerdir. Su Kaşifi programına katılmayan gruplarda geleneksel fen müfredatı işlenirken, bu programa katılan gruplarda programın içindeki projeler uygulanmıştır. Çalışma öncesi ve sonrasında tüm gruplara su kullanım tutumu, su kullanım davranışı ve çevre bilinci testleri uygulanmıştır. Testlere ek olarak, Su Kaşifi gruplarına açık uçlu çalışma kağıtları verilmiştir. Çalışmanın sonuçları, Su Kaşifi programına katılan grupların, tüm testlerde programa katılmayan diğer gruplardan anlamlı derecede daha iyi olduğu yönündedir. Bu nedenle öğrencilerin su kullanımı, davranışı ve çevre bilincinin arttırılması için fen müfredatında bu tür projelere yer verilmelidir.
Tez (Yüksek Lisans) - Yıldız Teknik Üniversitesi, Sosyal Bilimler Enstitüsü, 2019
Keywords: Su kaşifi; Sürdürülebilir kalkınma; STEAM; Su tasarrufu; Water explorer; Sustainable development; Water saving; Environment education